2014
DOI: 10.1186/1745-6215-15-345
|View full text |Cite
|
Sign up to set email alerts
|

A combination of ascorbic acid and α-tocopherol to test the effectiveness and safety in the fragile X syndrome: study protocol for a phase II, randomized, placebo-controlled trial

Abstract: BackgroundFragile X syndrome (FXS) is an inherited neurodevelopmental condition characterised by behavioural, learning disabilities, phisical and neurological symptoms. In addition, an important degree of comorbidity with autism is also present. Considered a rare disorder affecting both genders, it first becomes apparent during childhood with displays of language delay and behavioural symptoms.Main aim: To show whether the combination of 10 mg/kg/day of ascorbic acid (vitamin C) and 10 mg/kg/day of α-tocophero… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 88 publications
0
4
0
2
Order By: Relevance
“…These findings are compelling because such supplements are easy to recommend, although studies of patients with FXS have not been completed. A randomized controlled trial of alpha tocopherol (10 mg/kg/day) combined with vitamin C (10 mg/kg/day) is currently being carried out in Spain by de Diego-Otero et al [31] lasting 12–24 weeks for boys with FXS aged 6–18 years (ClinicalTrials.gov Identifier: NCT01329770).…”
Section: Omega 3 and Other Neutraceuticalsmentioning
confidence: 99%
“…These findings are compelling because such supplements are easy to recommend, although studies of patients with FXS have not been completed. A randomized controlled trial of alpha tocopherol (10 mg/kg/day) combined with vitamin C (10 mg/kg/day) is currently being carried out in Spain by de Diego-Otero et al [31] lasting 12–24 weeks for boys with FXS aged 6–18 years (ClinicalTrials.gov Identifier: NCT01329770).…”
Section: Omega 3 and Other Neutraceuticalsmentioning
confidence: 99%
“…Thus, the cross-talk of iNOS, nNOS, and NF- κ B is suggested in neurological processes. Several neurological and inflammatory disorders have been linked to NF- κ B, therefore restoring the nitric oxide/nitrosative status, and also to REDOX equilibrium on the FXS which addresses a promising approach for further investigation on treatment trials for the disease as has been also suggested in previous recent publications [ 45 , 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…También se ha propuesto una posible disfunción colinérgica en el síndrome X frágil que podría estar implicada en la sintomatología y han descrito que el ensayo con donezepil, un inhibidor de la acetilcolinesterasa, mejora Mejoría tanto en el placebo como en el tratamiento (Paribello et al, 2010;Leigh et al, 2013) NTC 01120626 No hay mejoría en los test de inteligencia y comportamentales (Sahu et al, 2013) Fuente: actualizado del artículo de De Diego Otero et al, 2014. significativamente funciones cognitivas y de comportamiento en pacientes afectados. Ensayos de tratamiento han comprobado la efectividad parcial de distintos compuestos, como el litio, que ha demostrado eficacia para mejorar el comportamiento y el aprendizaje (Ligsay y Hagerman, 2016: 158).…”
Section: A B C 3 Avances En Investigación Y Tratamientos Experimentalesunclassified
“…En modelos animales FMR1-KO se observan exceso de radicales libres dependientes de NADPH-oxidasa que provoca elevación del estrés oxidativo a nivel del sistema nervioso central. Estas alteraciones podrían estar relacionadas con la hiperactividad, el trastorno ansioso y el déficit cognitivo o del lenguaje, pues con la utilización de compuestos reguladores de esta vía fisiopatológica se consigue revertir parcialmente el fenotipo (De Diego Otero et al, 2009: 1011Romero-Zerbo et al, 2009: 224;De Diego Otero et al, 2014).…”
Section: A B C 3 Avances En Investigación Y Tratamientos Experimentalesunclassified